2019
DOI: 10.1007/s00253-019-09777-0
|View full text |Cite|
|
Sign up to set email alerts
|

Mutations in AraR leading to constitutive of arabinolytic genes in Aspergillus niger under derepressing conditions

Abstract: The AraR transcription factor of Aspergillus niger encodes a Zn(II) 2 Cys 6 transcription factor required for the induction of genes encoding arabinolytic enzymes. One of the target genes of AraR is abfA , encoding an arabinofuranosidase. The expression of abfA as well as other L-arabinose-induced genes in A. niger requires the presence of L-arabinose or its derivative L-ara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…We previously used forward genetic screens based on promoter- amdS reporter constructs, to isolate mutants showing constitutive expression of pectinase (Niu et al 2017 ) and arabinase encoding genes (Reijngoud et al 2019 ). To obtain insight into the transcriptional regulation of faeB , a similar strategy was used in which PfaeB-amdS and PfaeB-lux double reporter strains were constructed with the aim to identify mutants displaying constitutive, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…We previously used forward genetic screens based on promoter- amdS reporter constructs, to isolate mutants showing constitutive expression of pectinase (Niu et al 2017 ) and arabinase encoding genes (Reijngoud et al 2019 ). To obtain insight into the transcriptional regulation of faeB , a similar strategy was used in which PfaeB-amdS and PfaeB-lux double reporter strains were constructed with the aim to identify mutants displaying constitutive, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In chapter 2, we have shown that accumulation of the inducers of XlnR and AraR does not automatically result in higher expression of the xylanolytic and arabinolytic genes compared to the reference strain, probably due to their repression mediated by the carbon catabolite repressor protein CreA. Nevertheless, the constitutively active XlnR was recently shown to increase production of Carbohydrate-Active enZymes (CAZymes) and pentose release from WB , while the constitutively active AraR resulted in constitutive production of arabinanolytic enzymes under derepressing conditions (Reijngoud et al, 2019). Therefore, combination of targeted metabolic mutations with manipulation of these two TFs could improve production of CAZymes, and subsequently the release of D-xylose and L-arabinose from WB to improve xylitol and L-arabitol production.…”
Section: Application Opportunities Of the Experimentally Validated A ...mentioning
confidence: 93%
“…However, these processes require cautious control of growth conditions and long incubation times, while most microorganisms also consume cellulose and hemicellulose to support their growth [3]. These drawbacks prevent the industrial use of biological methods, although they are used in fields of biotechnology not covered in this review, such as bioremediation approaches [49][50][51].…”
Section: Pretreatment Of Biomass To Improve Enzymatic Depolymerizationmentioning
confidence: 99%
“…Constitutively active XlnR leads to increased production of plant biomass degrading enzymes, and D-xylose and L-arabinose release from wheat bran [44]. The constitutively active AraR has also been shown to result in constitutive production of arabinanases under derepressing conditions [49]. Therefore, these two regulators could be manipulated to increase the production of plant biomass degrading enzymes, and subsequently the release of D-xylose and L-arabinose from…”
Section: Xylitol Accumulation By a Niger From Diverse Lignocellulosic...mentioning
confidence: 99%
See 1 more Smart Citation